2009
DOI: 10.3174/ajnr.a1660
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Thalamic Radiations between 34 and 41 Weeks' Gestation: A Combined Voxel-Based Study and Probabilistic Tractography with Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE:This study aimed to investigate brain maturation along gestational age with diffusion tensor imaging in healthy preterm and term neonates. Therefore, a voxel-based study of fractional anisotropy (FA) and mean diffusivity (D av ) was performed to reveal the brain regions experiencing microstructural changes with age. With tractography, the authors intended to identify which fiber tracts were included in these significant voxels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 47 publications
10
65
0
Order By: Relevance
“…[72][73][74] Another hypothesis is that our results may have been influenced by the effect of prematurity. Indeed, even if the normality of our preterm population was based on robust structural and clinical criteria, as in previous studies, 48,52 we cannot exclude the possibility that the sex related differences observed in the language and motor networks may have been caused by subtle cerebral lesions, because certain studies seem to suggest that preterm males may be more sensitive to brain injuries than females. 75,76 Therefore, it would be of interest to investigate whether these sex differences are also present in healthy term neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[72][73][74] Another hypothesis is that our results may have been influenced by the effect of prematurity. Indeed, even if the normality of our preterm population was based on robust structural and clinical criteria, as in previous studies, 48,52 we cannot exclude the possibility that the sex related differences observed in the language and motor networks may have been caused by subtle cerebral lesions, because certain studies seem to suggest that preterm males may be more sensitive to brain injuries than females. 75,76 Therefore, it would be of interest to investigate whether these sex differences are also present in healthy term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…51 Finally, the obtained connectivity distributions were thresholded with a probability of 2%. 48,52,53 We calculated the TBV by measuring the volume of the voxels located in the brain mask. 14,54 To assess tract macrostructure, tract volumes and relative tract volumes (defined as the ratio between individual tract volume and TBV) were computed.…”
Section: Probabilistic Tractographymentioning
confidence: 99%
“…To our knowledge, there have been no studies assessing the CSTs in infants with focal lesions using tractography in the neonatal period. Furthermore, there have been few tractography studies assessing the healthy infant brain [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…An imaging data base and clinical record review during 3 years (January 2007-January 2010) yielded 24 very preterm infants (Ͻ30 weeks) who underwent 3T MR imaging at term-equivalent age (38 -42 weeks) that used all 3 sequences, SE-T1WI, GRE-T1WI, and SE-T2WI, and had no neurologic symptoms at clinical follow-up at 9 months of age or older (as determined by a pediatric neurologist), based on inclusion criteria from a previous study with a similar patient population. 7 Of the 24 patients from the data base search, 13 were excluded at initial review: 9 due to MR imaging abnormalities such as hypoxic-ischemic insult or T1-bright periventricular foci (n ϭ 4), germinal matrix or paren-chymal hemorrhage (n ϭ 3), periventricular leukomalacia (n ϭ 1), or a congenital structural abnormality (n ϭ 1). The remainder of excluded patients were due to suboptimal imaging or severe motion (n ϭ 4).…”
Section: Methodsmentioning
confidence: 99%